Development of a Smart Cricket Ball for Advanced Performance Analysis of Bowling. (2015) - Doljin, Batdelger; Fuss, Franz Konstantin
Abstract: Cricket bowling requires high level of skills in many ways (e.g. physically and mentally). The ball delivery technique is one of these important skills which can be optimised with advanced training methods. These training methods hinge on advanced performance parameters. Development of a low cost smart cricket ball will address the shortcomings of the existing systems and discover and explore cricket bowling kinematics and dynamics. In the past cricket bowling kinematics has not been properly studied using instrumented balls due to technical limitations of sensor system and electronics design. The aim of the project was to develop a highly portable instrumented cricket ball for recording the ball's kinematics and calculating dynamic performance parameters from kinematic data. The ball is designed in such a way that it exactly feels and looks (i.e. mass and material) as a real cricket ball. The ball is constructed from leather hemispheres, an impact proof Nylon6/6 nutshell, a shock damping foam material, and miniaturized electronics circuit.